USING GUESSING GAME IN TEACHING ENGLISH FOR YOUNG LEARNERS - Husni, Na'imatul; Lestari, Putri Maisaroh (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2024)
This research analyzed the use of “Guessing” games as a technique in teaching English speaking for young learners for Elementary students. The objectives of the study were to describe how the guessing game was applied in teaching speaking. In this study, the writer used Action Research and qualitative method with simple counting in presenting the data. To gather the data, the writer applied a classroom observation which was supported by questionnaires, tests, and field notes. The observation was conducted to the teaching of the fifth grade students of Fajar Siddiq, Palembang City. The writer concluded that there were some advantages of using the game of Guessing games such as enlarging knowledge, enriching vocabulary, receiving and sending message, and also problem solving. It is a simple interesting game and can motivate the students’ speaking habit to communicate in English with each other. The disadvantage was it could waste the time if the teacher could not use the time effectively and efficiently. Finally, the writer suggested that the teacher should apply interesting techniques or methods in her/his teaching. He/she also can apply the game of Guessing Game as a technique in teaching speaking or oral test for Elementary students.